USE OF PREFABRICATED MANDIBULAR ADVANCEMENT DEVICE FOR TREATMENT OF SLEEP APNEA SYNDROME IN INTERCITY TRANSPORT DRIVER: case report - Rocha Fernandes, Antônio Luiz; da Rosa Rambo, Tiago; Diehl, Bruna Eduarda; Ali Juma Hamid, Rafik; Wagner, Litiele Evelin; Romão Vieira Morinélli, Alexander; Mohammad Kamal Mansour, Kamila; Paiva, Dulciane Nunes (Revista Interdisciplinar de Promoção da Saúde, 2024)
Introduction: in obstructive sleep apnea syndrome there are obstructions in the upper airway that cause desaturation, sleep disorders and an increased risk of involvement in car accidents due to poor sleep quality. The mandibular advancement device is one of the therapeutic alternatives for this syndrome. Objective: to evaluate the effects of mandibular advancement device in an intercity public transport driver with obstructive sleep apnea syndrome. Methods: this is a case report of an individual submitted to mandibular advancement device for a period of eight weeks. The Epworth Sleepiness Scale, the Apnea-Hypopnea Index were evaluated using the polysomnographic profile, and the quality of life using the SF-36 questionnaire. The severity of obstructive sleep apnea syndrome was defined by the Apnea-Hypopnea Index (mild: ≥ 5 and ≤ 14; moderate: ≥ 15 and ≤ 29; severe: ≥ 30). Results: there was a reduction in the Apnea-Hypopnea Index from moderate to normal (16.0 → 1.8 ev/h), a reduction in the Epworth Sleepiness Scale (5 → 3), an increase in the domains of the quality of life questionnaire in the domains of functional capacity (65 → 90), physical limitations (75 → 100), general condition (30 → 35), vitality (50 → 55), emotional aspects (33 → 100) and mental health (52 → 76). Conclusion: there was a reduction in the severity of obstructive sleep apnea syndrome and sleepiness and an increase in quality of life after the use of the mandibular advancement device by intercity public transport drivers.